Academic Senate Minutes 2009-09-03 - Academic Senate:::::::::
Chair Report. Agenda Approved. Minutes of 5/7 and 5/21 – Approved. Faculty Eligible for Emeritus Status – Approved. Resolution on Giving Priority to Reports at the Senate – First Reading. Chair-Elect Report. Associated Students Report. Statewide Senators Report. President Report. Provost Report. Vice President of Administration and Finance Report. Vice President for SAEM report. CFA Report. Discussion of four day teaching modules. Group photo for website.